2019
DOI: 10.1080/10548408.2019.1661329
|View full text |Cite
|
Sign up to set email alerts
|

Understanding travel risks in a developing country: a bottom up approach

Abstract: This paper explores travel risk associated with natural disasters focusing on a developing country context using a bottom-up approach. A mixed method was used to identify seven travel risk types from tourists' perspective. The exploratory sequential design was applied to 52 respondents in the qualitative phase and 605 respondents in the quantitative phase. The study area was West Sumatra, Indonesia, a popular tourist destination that is prone to natural disasters. This study found different dimensions of trave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 79 publications
0
13
0
Order By: Relevance
“…Although health and disaster most likely to sharpen tourist's travel risks for vulnerable traveler [3,28,29], our study reveal that travelling was identified as an activity that stimulate the positive emotions and support to improve traveller's mental health issue. This show that travelling shape tourist's positive emotion such as in a short vacation [20,30].…”
Section: Conclusion Implication and Future Studymentioning
confidence: 81%
See 1 more Smart Citation
“…Although health and disaster most likely to sharpen tourist's travel risks for vulnerable traveler [3,28,29], our study reveal that travelling was identified as an activity that stimulate the positive emotions and support to improve traveller's mental health issue. This show that travelling shape tourist's positive emotion such as in a short vacation [20,30].…”
Section: Conclusion Implication and Future Studymentioning
confidence: 81%
“…Natural disaster is unpredictable and prone to have an undesirable effect on human psychology. Literature showed that natural disaster formed the traveler's emotion [1][2][3]. For example, post traumatic syndrome distress, performed as one of emotion by affected people.…”
Section: Introductionmentioning
confidence: 99%
“…The result is in line with research conducted by Sopyan & Widiyanto, (2015), and Mostafavi Shirazi & Mat Som (2010) [10] [24], although their research did not explain in detail which tourist attraction influences the re-visit intention. Besides, according to Lenggogeni, et al (2019) travel risk is an important factor to re-visit intention [25].…”
Section: The Effect Of Natural Attraction On West Sumatra's Tourist Rmentioning
confidence: 99%
“…Most tourism studies are exploratory-based research papers in nature (i.e., Devianto, Ridho, Maryati, & Lenggogeni, 2019;Filimonau & Mika, 2019;Mason, Augustyn, & Seakhoa-King, 2010;Nunkoo & Ramkissoon, 2011). There are many development research theories, such as a new scale development in tourism study (for instance, Lenggogeni, Ritchie, & Slaughter, 2019), which is often applied in the complex multiple regression-based research framework (Lenggogeni, 2015;Lenggogeni & Saito, 2018).…”
Section: Structural Equation Modelling In Tourism Research and Theorymentioning
confidence: 99%